A relação dialógica entre a educomunicação e a formação humana em Paulo Freire: uma análise sobre o protagonismo juvenil do Programa Conexões Periféricas - Brasil, Isabel Mayara Gomes Fernandes (2019)
The present study aims to understand the possibility of youth protagonism, from the educomunicative formation of the Conexões Periféricas/Rede Cuca Program. The approximations between educommunication and human formation in Paulo Freire trace a path in search of this main understanding. Starting from this proposal, the study undertakes to present a brief historical panorama of educommunication and its meetings with social movements, media-education, popular communication and popular education. Therefore, it is based on the assumption that educommunication, when articulated by social movements, absorbed in its epistemological basis the presuppositions of the educator Paulo Freire. To reach the central understanding, the youth protagonism, the study is based on three thematic categories: dialogicity, autonomy and empowerment, and its subcategories, in order to understand the category of youth protagonism within the context of the formation analyzed. Of qualitative nature, the research used the resources of the semi-structured individual interviews, with six members of the Conexões Periféricas Program, three of old seasons and three of the current season, combined with participant observation, between September and December 2018, during the validity of the 4th season. The analysis of the data was in charge of the proposal of the storm of light analysis of the discourse, which used the path of unitarization, categorization and new understanding for the construction of the last chapter. The work is Freirean in nature, having its bases supported by educator Paulo Freire, and counts on the valuable contribution of Ismar de Oliveira Soares (Educommunication), Cecília K. Peruzzo (Popular Communication), Carlos Rodrigues Brandão (Popular Education), Maria da Glória Marcondes Gohn (Social Movements), Mário Kaplún (Educommunication), Jesús Martín-Barbero (Educommunication), Cecília Minayo (Qualitative Research), Roque Moraes (Storm of Light), Pierre Bourdieu (Youths), among others. The results show positive and negative aspects of the analyzed experience and the research points to the possible collaborations in the aspects to improve. They indicate that young people have established connections between their activities and conceptions of dialogue, autonomy and empowerment, sometimes, but not in their entirety. Also, relate the formative practices to the opportunity to play a leading role within the Peripheral Connections. According to the young people and the observed experience, the program stimulates the protagonism in certain conditions, and in others, limits. Given this discussion, the term controlled autonomy appeared in the speech of young people, which makes an analytical parallel to the autonomy proposed by Paulo Freire and other authors, which ends up interfering with the understanding of youth protagonism.